Analisis Kualitas Produk, Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Garden Petshop Teleng Cikarang - Ika Sriyanti; Syahrul Alim (IPM2KPE, 2023)
This research aims to determine the analysis of product quality, price and service quality for Garden Petshop Teleng Cikarang. The type of research used in this research is quantitative. The results of the research show (1) There is a positive and significant influence of product quality on customer satisfaction at Garden Petshop Teleng Cikarang, as evidenced by the calculated t value of 4.382 with a sig value of 0.000 < 0.05 (2) There is a positive and significant influence of price on customer satisfaction at Garden Petshop Teleng Cikarang, as evidenced by the calculated t value of 2.932 with a sig value of 0.004 < 0.05 (3) There is no positive and insignificant influence between service quality on customer satisfaction, as evidenced by the calculated t value of 1.148 with a sig value of 0.254 > 0.05. The most dominant variable influencing customer satisfaction is product quality. In conclusion, it proves that the better the product quality, the more customer satisfaction will increase. Keywords: Price, Service Quality, Customer Satisfaction, Product Quality